Global responses of Il-1β-primed 3D tendon constructs to treatment with pulsed electromagnetic fields - Gehwolf, Renate; Schwemberger, Bettina; Jessen, Malik; Korntner, Stefanie; Wagner, Andrea; Lehner, Christine; Weissenbacher, Nadja; Tempfer, Herbert; Traweger, Andreas (Cells, 2019)
Tendinopathy is accompanied by a cascade of inflammatory events promoting tendon degeneration. Among various cytokines, interleukin-1β plays a central role in driving catabolic processes, ultimately resulting in the activation of matrix metalloproteinases and a diminished collagen synthesis, both of which promote tendon extracellular matrix degradation. Pulsed electromagnetic field (PEMF) therapy is often used for pain management, osteoarthritis, and delayed wound healing. In vitro PEMF treatment of tendon-derived cells was shown to modulate pro-inflammatory cytokines, potentially limiting their catabolic effects. However, our understanding of the underlying cellular and molecular mechanisms remains limited. We therefore investigated the transcriptome-wide responses of Il-1β-primed rat Achilles tendon cell-derived 3D tendon-like constructs to high-energy PEMF treatment. RNASeq analysis and gene ontology assignment revealed various biological processes to be affected by PEMF, including extracellular matrix remodeling and negative regulation of apoptosis. Further, we show that members of the cytoprotective Il-6/gp130 family and the Il-1β decoy receptor Il1r2 are positively regulated upon PEMF exposure. In conclusion, our results provide fundamental mechanistic insight into the cellular and molecular mode of action of PEMF on tendon cells and can help to optimize treatment protocols for the non-invasive therapy of tendinopathies.